2011
DOI: 10.1080/00380768.2010.551281
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of soil application of carbonaceous adsorbents on dieldrin uptake by cucumber fruits

Abstract: The use of aldrin and dieldrin as pesticides was prohibited in 1975 in Japan. However, some of the soils still remain contaminated with dieldrin, because aldrin is easily oxidized to dieldrin and dieldrin is extremely stable in soil. In recent years, dieldrin at concentrations exceeding the limit set by the Food Sanitation Law of Japan (dieldrin < 0.02 mg kg -1 fresh weight) has been detected in cucumber fruits produced in some areas of Japan. We examined the effect of the soil application of selected adsorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…For AC materials, AC2 and AC3 were the most effective in reducing PCB concentrations given their larger specific surface area and mesoporous surface, while AC1 was less effective due to its granular shape. This result confirms that surface properties and textural characteristics impact the sorption properties of carbonaceous materials in contaminated soils [11,12,14,26,27]. Regarding the type of pollutants, no difference could be shown in terms of sequestration efficiency by the different carbonaceous materials probably because the physicochemical properties related to adsorption in soil such as lipophilicity are of the same order (about log Kow of 7).…”
Section: In Vitro Assessment Of Interactions Between Pollutants and C...supporting
confidence: 71%
“…For AC materials, AC2 and AC3 were the most effective in reducing PCB concentrations given their larger specific surface area and mesoporous surface, while AC1 was less effective due to its granular shape. This result confirms that surface properties and textural characteristics impact the sorption properties of carbonaceous materials in contaminated soils [11,12,14,26,27]. Regarding the type of pollutants, no difference could be shown in terms of sequestration efficiency by the different carbonaceous materials probably because the physicochemical properties related to adsorption in soil such as lipophilicity are of the same order (about log Kow of 7).…”
Section: In Vitro Assessment Of Interactions Between Pollutants and C...supporting
confidence: 71%
“…For example, partitioning into the roots is a function of root lipid content in addition to the hydrophobicity of the chemical [31]. Another example of species differences is the enhanced ability of "gold rush" zucchini (Cucurbita pepo, subspecies pepo) to transfer hydrophobic organics from roots to aboveground tissues, relative to other plants [32][33][34][35]. This enhanced root to shoot transfer is thought to be partly attributable to interactions with various proteins that increase the solubility of these compounds in the xylem sap [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of crops contaminated by persistent organic pollutants (POPs), including dieldrin and heptachlor exo-epoxide, showed that application of carbonaceous adsorbents, such as activated carbon, to soils [4][5][6] and a grafting technique using a low-uptake rootstock 4,7) effectively decreased concentrations of POPs in cucurbit crops. However, the pesticides on the market are more degradable than POPs in soils.…”
Section: Introductionmentioning
confidence: 99%